(untitled) (Pedagogy of Higher and Secondary Education, 2015)
Fentsyk O. M. The problem of epic studying in the literary education: historical and methodological review. The article deals with the problem of critical analysis of methodological heritage of literature teaching methods of the second half of the XX – beginning of the XXI century. The author examines basical scientific and methodological works on problems of epic work studying through measuring its content and form, identifies the most important scientific and methodical ideas of scientists which still occupy an important place in the theory and practice of literature teaching methods.